# SOLUTION: How do I solve this proof: If PQ=3(x-1), QR=7-2x and PR=6, then PQ=QR It is not stated that Q is the midpoint, though by setting up 3(x-1)=7-2x, you can figure out that it comes

Algebra ->  Algebra  -> Geometry-proofs -> SOLUTION: How do I solve this proof: If PQ=3(x-1), QR=7-2x and PR=6, then PQ=QR It is not stated that Q is the midpoint, though by setting up 3(x-1)=7-2x, you can figure out that it comes      Log On

 Ad: Algebra Solved!™: algebra software solves algebra homework problems with step-by-step help! Ad: Algebrator™ solves your algebra problems and provides step-by-step explanations!

 Geometry: Proofs in Geometry Solvers Lessons Answers archive Quiz In Depth

 Click here to see ALL problems on Geometry proofs Question 379894: How do I solve this proof: If PQ=3(x-1), QR=7-2x and PR=6, then PQ=QR It is not stated that Q is the midpoint, though by setting up 3(x-1)=7-2x, you can figure out that it comes to 3=3, but because it isn't stated that Q is the midpoint, I can't put down my reason as "Definition of midpoint". I really need help.Answer by richard1234(5390)   (Show Source): You can put this solution on YOUR website!From solving, x = 2, and we have PQ = QR = 3. Even though it's not stated in the problem that Q is the midpoint, we already know it is from solving for x, and showing that PQ = QR.